Perlindungan Hukum Bagi Korban Tindak Pidana Cyber Sekstorsi Di Indonesia (Studi Kasus Rebecca Klopper) - Ghani, Muhammad Yusuf Al; Saefudin, Yusuf (Universitas Sultan Ageng Tirtayasa, 2024)
The development of electronic media and information technology is increasingly rapid in contemporary globalisation. Cybercrime is a word used to describe the misuse and adverse effects of the development of information technology through computerised systems and internet networks. Sextortion is a type of gender-based cybercrime in which the victim is blackmailed using sexually suggestive images or videos, as happened to Rebecca Klopper, whose case recently went viral. This research is designed using the normative juridical method, or the approach used is the statute approach, data sourced from laws and regulations which are qualitatively analysed and presented with descriptive analysis. Based on the results of the study, victims of extortion are recognised as receiving legal protection in the Criminal Code, specifically Article 368 paragraph (1) related to extortion and Article 369 paragraph (1) related to threatening acts. If the elements of the criminal offence of extortion and threatening are proven and convincing in accordance with the provisions of the legislation, then the elements of extortion and threatening in Article 27 paragraph 4 of the Electronic Transaction Information Law immediately apply. In addition, Article 14 paragraphs (1) and (2) of the Sexual Violence Law provides for six years of imprisonment for similar offences. To identify cybercrimes in the form of extortion that can be considered as international crimes, this research is also equipped with several countermeasures that can be implemented by victims of cybersexual violence.